2011
DOI: 10.1007/s11934-011-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Rise of Herbal and Traditional Medicine in Erectile Dysfunction Management

Abstract: Herbal medicine long has been used in the management of sexual dysfunction, including erectile dysfunction. Many patients have attested to the efficacy of this treatment. However, is it evidence-based medicine? Studies have been done on animal models, mainly in the laboratory. However, randomized controlled trials on humans are scarce. The only herbal medications that have been studied for erectile dysfunction are Panax ginseng, Butea superba, Epimedium herbs (icariin), Tribulus terrestris, Securidaca longiped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 60 publications
(52 reference statements)
1
44
0
2
Order By: Relevance
“…20,22,[25][26][27] Because ginseng is not a drug that can treat severe ED, we enrolled mild-to-moderate ED patients only. We found that SKGB group showed improvement after 8 weeks of treatment by within-group analysis.…”
Section: Discussionmentioning
confidence: 99%
“…20,22,[25][26][27] Because ginseng is not a drug that can treat severe ED, we enrolled mild-to-moderate ED patients only. We found that SKGB group showed improvement after 8 weeks of treatment by within-group analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidencebased sexual drug treatment has increased tremendously over the past two decades, and despite effective well-established treatment options for ED, many patients are still dissatisfied. 17 Dropout rates for current medical therapies are high, and overall satisfaction is below expectation due to drug inefficiency and adverse events such as headache and hot flashes. Further, while ED can generally be treated successfully using current treatment options, it cannot be cured.…”
Section: Pro-erectile Effects Of Ginseng Berry Ks Cho Et Al 505mentioning
confidence: 99%
“…Though herbal medicines are not a prescribed option of choice for patients in the United States, in other parts of the world like Asia, Africa and the Middle East, it is a widely used form of therapy for men with ED [44]. However, although there are a myriad of herbal treatments that are very appealing for patients with ED, caution must be warranted, since some herbal medicines may cause deleterious drug interactions, especially in men with comorbid diseases such as CV and diabetes.…”
Section: Herbal Treatment For Ed (Yohimbine)mentioning
confidence: 99%
“…On the other hand, the herbal or traditional therapeutic approach may be more culturally acceptable with some patients, who may prefer this holistic option because of religious, social, monetary or other personal preferences. As a result, there is a growing interest among the population for alternative holistic treatment options, which has increased demand for such therapies in the United States [44]. Though there are many herbal remedies available at present for ED, this review will focus on the efficacy of yohimbine.…”
Section: Herbal Treatment For Ed (Yohimbine)mentioning
confidence: 99%
See 1 more Smart Citation